The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3906/kim-2002-76
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, structure elucidation, and antioxidant activity of new bis(thiosemicarbazone) derivatives

Abstract: Schiff-base-bearing new bis(thiosemicarbazone) derivatives were prepared from terephthalaldehyde and various thiosemicarbazides. FT-IR, 1 H NMR, 13 C NMR, and UV-Vis spectroscopic methods and elemental analysis were used to elucidate the identification of the synthesized molecules. The in vitro antioxidant activity of the synthesized compounds was analysed with the 1,1-diphenyl-2-picryl hydrazyl free-radical-trapping process. The synthesized compounds exhibited lower antioxidant activity than the standard asco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 33 publications
5
14
0
Order By: Relevance
“…The frequency data of all of the molecules were consistent with those reported for similar compounds. [1,18,19]…”
Section: Vibrational Frequenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency data of all of the molecules were consistent with those reported for similar compounds. [1,18,19]…”
Section: Vibrational Frequenciesmentioning
confidence: 99%
“…They have shown a wide spectrum of biological and medicinal properties such as antibacterial, [ 11 ] antiviral, [ 12 ] antimicrobial, [ 13 ] anticancer, [ 14 ] antituberculosis, [ 15 ] anticonvulsant, [ 16 ] urease inhibitory activity, [ 17 ] and antioxidant agents. [ 18–20 ] Recently, it has been revealed that thiosemicarbazones containing glyoxalic acid and isatin 2‐indolinones exhibit good inhibition against carbonic anhydrases (CAs). [ 21,22 ]…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 shows some previously published thiosemicarbazide and thiosemicarbazone derivatives with anticancer and antimicrobial activities. Thiosemicarbazide and thiosemicarbazone derivatives are privileged moieties of profound interest in medicinal chemistry, as they possess different biological activities, such as anticancer (Bonaccorso et al, 2018), antimicrobial (Vekariya et al, 2017), antifungal (G. Yang et al, 2018), and antioxidant (Yakan, 2020) activities. Triapine VII and Dp44mT VIII are synthetic thiosemicarbazone analogs that have been reported to be potent anticancer agents (Finch et al, 2000; Krishan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…They are also used as versatile intermediates for synthesizing numerous compounds. They have shown a broad spectrum of chemical, biological and medicinal properties such as anti‐HIV, [11] antimicrobial [12] antiviral, [13] antibacterial, [14] anticonvulsant, [15] anticancer, [16] urease inhibitory activity, [17] antituberculosis, [18] cytotoxic activity, [19] and antioxidant agents [20–22] …”
Section: Introductionmentioning
confidence: 99%